Pemanfaatan Waktu Belajar oleh Pengurus Organisasi Siswa Intra Sekolah (OSIS) - Elinnawati Elinnawati; Khairani Khairani (Jurnal Neo Konseling, 2019)
Utilization of study time is important for students. If students cannot use the time to study well this will have a negative impact on their learning outcomes. The reality in the field found that several students who were administrators of the Student Council had not used the time to study well. This is because students are more preoccupied with organizational activities. This study aims to describe the utilization of learning time by the OSIS management which includes 1) making a schedule and its implementation, 2) reading and making notes, 3) repeating the lesson material, 4) concentration and 5) working on the task.The type of research used is descriptive quantitative research. The research subject was the board of student council of SMAN 2 Padang in the 2018/2019 academic year, which was 38 people. The research data was collected using a questionnaire. Data analysis techniques that use percentage techniques.The research findings revealed 1) the utilization of study time by the OSIS administrators in terms of making schedules and their implementation was in a fairly good category, 2) the utilization of study time by the student council administrators in terms of reading and taking notes in a fairly good category, 3) utilization of study time by administrators OSIS in terms of repeating the subject matter is in the fairly good category, 4) the utilization of study time by the OSIS administrators in terms of concentration is in a fairly good category and 5) the utilization of study time by the OSIS administrators in terms of doing assignments is in a fairly good category. Based on the research findings, it can be concluded that the utilization of study time by the Student Council administrators is in a fairly good category.